New synthesized phosphazenes containing chalcone on human prostate cancer cell lines: An in vitro study - Tekin, S.; Koran, K.; Ozen, F.; Sandal, S.; Cil, E.; Gorgulu, A. O. (Wiley-Blackwell, 2014)
[Abstract Not Available]
Keywords: Phosphazene; Chalcone; PC-3; LNCaP; Cell viability; MTT assay